(untitled) (Journal of actual problems of jurisprudence, 2020)
This article discusses the main problems that arise in the activities of law enforcement agencies when using a polygraph (lie detector). It is proved that the survey using a polygraph is a procedure for assessing the subjective исчисляютсяsignificance of the stimulus, and therefore the need to include this procedure in the system of methods and means of domestic forensic psychological examination is justified. To date, tthe instrumental method of psychophysiological detection of hidden information, in other words, examination using a polygraph (lie detector), is widely used in the Republic of Kazakhstan. According to the public Association «Eurasian Аssociation of polygraph examiners», only in 2015, law enforcement agencies and special services of Kazakhstan put into operation at east 75 new polygraphs of various systems and models. The training center of the Association has trained 168 polygraph specialists for all law enforcement agencies. It is worth noting that the use of scientific and technical means contributes to the rapid and effective detection of crimes, as well as reducing the number of judicial errors. In criminology and the practice of operational investigative activities, the use of methods borrowed from other disciplines is of great importance. Currently, more than fifty countries around the world (USA, Japan, Canada, Israel, Turkey, Poland, Hungary, etc.) use methods of registering psychophysiological reactions of people in order to establish their involvement in crimes using polygraphs. Key words: polygraph, operational-search activity, lie detector, disclosure and investigation of crimes, psychophysiological method.